Real-time structural health monitoring of fatigue crack on aluminum beam using an impedance-based portable device. (December 2017) - de Souza Rabelo, Diogo; Hobeck, Jared D; Inman, Daniel J; Finzi Neto, Roberto Mendes; Steffen, Valder
A common problem in aircraft maintenance is the development and detection of fatigue cracks in structural components with localized high-stress concentration. Traditional non-destructive testing methods are effective in inspecting cracks through an offline manner; however, real-time implementation of these methods is not common. In this contribution, a procedure to monitor propagating cracks in aluminum beams undergoing dynamic cyclic loading is presented. High-frequency impedance measurements were performed from a lead zirconate titanate patch bonded to an aluminum beam while the beam experienced cyclic loading at a prescribed amplitude. Fatigue loading at prescribed stress levels was achieved by exciting the beam with an electromechanical shaker. A control scheme was used to keep the drive frequency and drive acceleration under resonance in the first vibration mode. During the tests, impedance measurements were acquired using a low-cost portable impedance device. Damage indices were correlated with the specific number of stress cycles until changes in the natural frequency caused by propagating fatigue cracks reached a critical limit. Finally, a statistical method is proposed to obtain the damage threshold. Based on S/N curves, the determined threshold was compared to the damage indices so that incipient damage could be detected before a visible crack could be seen.